Primary sleep disorder prevalence in patients with newly diagnosed Parkinson's disease. Issue 2 (4th November 2013) - Prudon, Benjamin; Duncan, Gordon W.; Khoo, Tien K.; Yarnall, Alison J.; Burn, David J.; Anderson, Kirstie N.
ABSTRACT Background Sleep disturbance occurs in up to 96% of patients with established Parkinson's disease (PD). We aimed to assess the prevalence of sleep disturbance in newly diagnosed PD. Methods Newly diagnosed PD patients and controls were recruited. Patients had motor, non‐motor, and sleep assessments, including sleep questionnaires, respiratory home monitoring, actigraphy, and sleep diaries. Controls completed cognitive assessments, sleep questionnaires, and diaries. Results A total of 106 patients and 99 controls participated. Sleep questionnaire scores were no different between patients and controls. Daytime naps were increased in PD patients on sleep diaries (P > 0.003). Sleepiness was not associated with any motor or non‐motor symptom. Periodic limb movements were increased but not associated with restless legs. Conclusions Newly diagnosed PD patients had minimal differences in subjective or objective sleep disturbance compared to controls apart from increased daytime naps and symptoms such as dream‐enacting behaviors of punching or grabbing. This contrasts with the literature assessing sleep in those with established PD.© 2013 International Parkinson and Movement Disorder Society